Creative safety solutions - Schneid, Thomas D. (Boca Raton : Lewis Publishers, 1999)
Creative Safety Solutions presents innovative ways to solve complex safety and health problems in the office or factory. The key to its distinctive approach is to motivate employees to "think safety" by encouraging active involvement in safety, health, and loss prevention; considering innovative ways to solve common problems; learning from case studies of successful safety and health programs in industry; and developing techniques to foster creative thinking.
Ch. 1. Introduction -- Ch. 2. Effective selling of safety and health programs -- Ch. 3. Creative safety equipment purchases -- Ch. 4. Tapping employee creativity -- Ch. 5. Traditional "things" -- Ch. 6. Involving the family -- Ch. 7. Involving the community -- Ch. 8. Establishing and using your network -- Ch. 9. Joint ventures to reduce costs -- Ch. 10. Grants, contracts, tax credits, and deductions -- Ch. 11. Utilizing free services -- Ch. 12. Using the Internet resources -- Ch. 13. Tapping other resources -- Ch. 14. Creative safety communication ideas -- Ch. 15. Acquiring university and student services -- Ch. 16. Looking outside the safety arena -- Ch. 17. Creative solutions to difficult problems -- Ch. 18. Creative safety programs -- App. A. Potential sources of assistance -- App. B. Employee workplace rights -- App. C. Targeted Hazard Identification System -- App. D. Sample action plan -- App. E. Sample safety audit assessment.
Includes bibliographical references and index.
Keywords: Industrial safety